Dragons, Riders of Berk. Volume 2, Dangers of the deep - Furman, Simon (Titan Comics, 2014)
When Stoick and all the grown-ups head off on a mission, Hiccup is left in charge. Sounds like fun? It is until Alvin the Treacherous decides to attack Berk. Meanwhile, in the scary Veil of Mists, Stoick and Co are attacked by a huge and deadly sea creature.